Mapping of Inbound Flows in Supply Chain of Lithium-ion Industry in Indonesia - Sutopo, Wahyudi; Zakaria, Roni; Wardayanti, Ari; Fahma, Fakhrina (http://dx.doi.org/10.31427/IJSTT.2018.1.1.3, 2018)
The demand for lithium battery is currently high from the consumer side due to the widespread application of lithium-ion battery for electronics (laptops, notebooks, mobile phones, street lighting) and electric vehicles (electric cars and electric motors). In Indonesia, the research and industrialization on lithium-ion battery have been conducted to develop products such as for electric vehicles and street lighting. On the other hand, the relationship between suppliers, producers, distribution channels, and consumers has not been mapped. This mapping is intended to provide an overview of the strength of suppliers, involved manufacturers, and to determine the readiness of the value chain of lithium-ion battery to perform mass production. The approach in the mapping uses primary data and secondary data for the initial stage of inbound flows in supply chain of lithium-ion industry in Indonesia. Primary data are obtained from the questionnaires, which adopted from the value chain lithium-ion battery research in USA adjusted for Indonesian context. Meanwhile, the secondary data derived from literature reviews. The respondents in the study are 11 institutions consisting of manufacturers and R&D of lithium-ion battery in Indonesia. The results obtained are supplier mapping that provides the flow of lithium-ion battery, cell, module, and pack as well as the producers and consumers. The results could also be utilized to identify the valuable metrics in the supply chain of lithium battery industry.